(Im)politeness as a Strategy in the Discursive Construction of In-Group Solidarity in Discussions about Love, Sex and Relationships on Incels.is - Olga O'Toole (Półrocznik Językoznawczy Tertium, 2024)
As a discourse community that is formed and maintained mostly online, involuntary celibates (who are typically heterosexual men) have been known to be one of the most obvious groups presenting misogynistic attitudes (Bates 2020). There are various forums where such online users meet to discuss subjects of relevance to them, including Reddit and subreddit threads (r/incels) and websites specifically targeted at the community (such as Incels.is). Although the subject of incel discourses has been addressed from several linguistic perspectives, including the representation of social actors (Heritage & Koller 2020), toxic language in the community (Pelzer et al. 2021), metaphor (Heritage et al. 2023) and the extreme language of misogyny (Bogetić 2022), still relatively little has been written specifically about how the community of practice is formed on the basis of the discursive expression of solidarity. The present paper is an analysis of discussions on the forum Incels.is on the subject of sex and relationships, specifically investigating how both manifestations of misogynist attitudes and discursive strategies of politeness are used to form solidarity between users. The analysis considers that through the employment of positive and negative politeness strategies in an online community, group bonds are made stronger and in-group solidarity is expressed both directly and indirectly. The analysis of politeness strategies showed that positive politeness and negative politeness were both present as face-saving acts and to construct solidarity through the use of sarcasm, kinship claiming, informal language and the negative evaluation of female actors.